Direct delivery of chemotherapeutic agents for the treatment of hepatomas and sarcomas in rat models - Pendas, S... (Radiology and oncology (Ljubljana), 1998)
The combination of a chemotherapeutic agent and electric pulses has been termed electrochemotherapy (ECT). This procedure is based on the premise that electric pulses can increase the uptake of molecules through the cell membranedue to permeabilization of the mebrane through a process called electroporation. This prodedure has been successful in increasing the effectiveness of anti-tumor agents (electrochemotherapy; ECT). Response rates of>80% have been obtained in both animal and human trials for several types ofskin malignancies using ECT with bleomycin. This study was initiated to determine if ECT could be used to effectively treat internal tumors such as hepatomas in an animal model and human rhabdomyosarcomas in athymic rats. Bleomycin, cisplatin, doxorubicin, 5-fluorouracil, and taxol were used in conjuction with electric pulses. Following an intra tumor injection of a single drug, electric pulses were administered directly to the tumor. For the hepatoma model, ECT worked the best with cisplatin and bleomycin, yielding complete response rates of about 70%. The other drugs used to treat hepatomas were ineffective. Bleomycin combined with electric pulses resulted in a 100% response rate for sarcoma; response rates with cisplatin and doxorubicin were low. These studies indicate that ECT is a technically feasible procedure for visceral tumors and soft tissue sarcomas.
Keywords: Bleomycin; Cisplatin; Doxorubicin; Drug therapy; Electric stimulation therapy; Fluorouracil; Hepatomegaly; Liver neoplasms, experimental; Rats; Rhabdomyosarcoma; Therapy